Evaluating rotations of winter annual and summer annual forages for yield, nutritional value, and economic sustainability as forage resources for beef cattle in northern Iowa - Denise Schwab; Josh Michel; Beth Reynolds; Ken Pecinovsky; Shelby Gruss (Hello World!, 2024)
Interest in grazing cover crops and winter annuals has increased in recent years. Research on grazing winter and summer annuals in Iowa has been concentrated in southern Iowa, but because of differences in growing conditions, data on growth potential from the northern half of the state is needed. Similar interest has been developing on utilizing summer annuals to maximize production during the summer slump of Iowa pastures. This project is designed to replicate the winter annual - summer annual project at the McNay, Armstrong and Neely-Kinyon research farms, in order to measure and demonstrate the applicability of a winter annual - summer annual forage rotation in northern Iowa at the 2023 Northeast Research and Demonstration Farm Progress Reports at Nashua.